(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Circumcision and its complications are one of the most common cases that pediatric surgeons facing in their practice. There are many techniques that have been described to perform it either by the free hand operative methods or with the use of special devices. Objective: To evaluate the results of using Gomco clamp for circumcision as a preliminary experience in Iraq. Methods: A total of 120 babies were subjected to circumcision by this device during the period from April 2014 - November 2015; their age ranges from 7 days - 11 months and they were divided into 3 groups: neonates, infants 1-3 months, infants 4-11 month. By using three different sizes of the clamp, the procedure was performed under local anesthesia in the majority of cases in a form of subcutaneous ring block with aid of sedatives while general anesthesia was given to those cases of coincidental circumcision with other operations. The outcomes of the procedure were assessed after one-month period of follow up. Results: 12.5% of cases were neonates; the average duration of the procedure was 20 minutes. A total complication rate of 9.16% was recorded (11 cases out of 120. The lowest rate of complication (6.6%) was seen in neonates, while the group of infants older than 4 months had the highest complication rate (10%). The most frequent complication recorded was bleeding (36.3% of all complication rate) followed by excess skin, infection, meatitis, epidermal inclusion cyst, no other complications were recorded. Conclusion: Circumcision by Gomco clamp is a safe and simple method with good functional and cosmetic results if performed during neonatal period and early infancy. Choosing the suitable size of the clamp, adequate training and good postoperative care will minimize most of the complications. Keywords: Circumcision, Gomco clamp, neonate, infant, complications. Citation: Ali E. Joda. Gomco clamp circumcision in neonates and infants: a preliminary experience in Iraq. Iraqi JMS. 2017; Vol. 15(2): 188-197. doi: 10.22578/IJMS.15.2.12